+0  
 
0
403
1
avatar

if y=3x and 4x - 2y=5, then x = ?

Guest May 17, 2017
 #1
avatar+87301 
+1

y = 3x      (1)

 

4x - 2y  =  5       (2)

 

Sub (1)  into (2)   and we have

 

4x - 2 (3x)  =  5    simplify

 

4x - 6x   = 5

 

-2x  =  5        divide both sides by -2

 

x  =   -5 / 2

 

 

cool cool cool

CPhill  May 17, 2017

15 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.